In Vitro Expansion of Keratinocytes on Human Dermal Fibroblast-Derived Matrix Retains Their Stem-Like Characteristics - Wong, C.; Kinnear, B.; Sobota, R.; Ramalingam, R.; Legrand, C.; Dye, Danielle; Raghunath, M.; Lane, B.; Coombe, D. (2018)
The long-term expansion of keratinocytes under serum- and feeder free conditions generally results in diminished proliferation and an increased commitment to terminal differentiation. Here we present a serum and xenogeneic feeder free culture system that retains the self-renewal capacity of primary human keratinocytes. In vivo, the tissue microenvironment is a major contributor to determining cell fate and a key component of the microenvironment is the extracellular matrix (ECM). Accordingly, acellular ECMs derived from human dermal fibroblasts, cultured under macromolecular crowding conditions to facilitate matrix deposition and organisation, were used as the basis for a xenogeneic-free keratinocyte expansion protocol. A phospholipase A2 decellularisation procedure produced matrices which, by proteomics analysis, resembled in composition the core matrix proteins of skin dermis. On these ECMs keratinocytes proliferated rapidly, retained their small size, expressed p63, did not express keratin 10 and rarely expressed keratin 16. Moreover, the colony forming efficiency of keratinocytes cultured on these acellular matrices was markedly enhanced. Collectively these data indicate that the dermal fibroblast-derived matrices support the in vitro expansion of keratinocytes that maintained stem-like characteristics under serum free conditions.